MENINGKATKAN HASIL BELAJAR IPA SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD KELAS V SD ST. ANTONIUS BANGUN MULIA TAHUN PELAJARAN 2017/2018 - SIREGAR, YUNIKO JULIANA (Jurnal Ilmiah Aquinas, 2018)
This research is intended to improve science learning outcomes by using STAD type cooperative learning model in grade V students of St. Antonius BangunMulia academic year 2017/2018. Subjects in doing this action are the researchers who work together with the homeroom as observers, while the object of this research is the students of grade V SD St. Antonius BangunMulia Medan which requires 35 students consisting of 15 men and 20 women. Data processing techniques through observation of the results of learning tests and student learning activities. The results of this study indicate an increase in student learning outcomes in science subjectspda material digestive system food in human class V St. Antonius BangunMulia Medan. This is evident from the results of research conducted on the pretest of students who get the complete value of 5 people or 14.29% while students who are not complete as many as 30 people or 85.71%. So began the research on the first cycle of students who got the complete value of 21 people or 60% while the unfinished students as many as 14 people or 40%, then an increase in the cycle I compared to the pretest. Will not meet the completed category of mastery already in the set. So began the research on cycle II of students who get thoroughly as many as 30 people or 85.71% while students who are not complete as many as 5 people or 14.29%, then there is an increase in cycle II depending on the cycle I and already meet the specified mastery. Furthermore, teacher activity on observation I giving cycle average of 60% and in cycle II has increased to 86%. While the student activity on the learning process resulted in an average of 60% and in cycle II has increased to 82%. Thus developed by using cooperative learning model type STAD science subjects on food system material in human grade V SD St. Antonius BangunMulia Medan can improve student learning outcomes. therefore it is recommended for subsequent learning to use STAD type cooperative learning model so that student learning outcomes can be improved